Foundations of a right to technological due process of law - Asís Pulido, Miguel de (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
In this paper, a philosophical-legal study of the right to due process of law recognized in article 24 of the Spanish Constitution is conducted in order to adapt this right to the Algorithmic Age. To achieve this goal, at first paragraph we review the history and legal foundation of due process of law on the Spanish juridical system. Then, at second paragraph, a consideration of the principles and guarantees intrinsic to a right to due technological process of law will be carried out. Finally, as a conclusion, a proposal of constitutional drafting will be advanced.
Keywords: Technological due process of law; Algorithmic systems; Justice digitalization; Artificial Intelligence; Judicial process; Due process of law